PELAKSANAAN PENYIDIKAN TINDAK PIDANA KECELAKAAN LALU LINTAS YANG MENYEBABKAN MATINYA KORBAN BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Amrinto Nainggolan; Erdianto '; Syaifullah Yophi A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Violation of traffic signs were done by the driver in the jurisdiction Pelalawan Resort is one of the causes of most cases of traffic accidents. Thus, the driver in this case should be held accountable as expressly by law enforcement (police) on the act of doing. Firmness that can be realized by doing the investigation on the accident that happened to pelalu can be prosecuted. However, it was evident when players can slip away from the law. The purpose of this thesis, namely; First, law enforcement against drivers who because of negligence has caused other people died in traffic accidents, in Region Resort Pelalawan Secondly, bottlenecks in the implementation of the law enforcement investigation does peace between the offender, the victim and the Traffic Police which resulted in the accident died cross, Third, efforts are being made to overcome the obstacles in the implementation of the law enforcement investigation that resulted in the driver of another person died in a traffic accident. This type of research can be classified as socio-juridical, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. In this study, source of data is the primary data, secondary data, and tertiary data, data collection techniques in this study with interview, questionnaire, and the study of literature. From the results of this study lead to death of the victim is a criminal matter and should be resolved in court. But in addition to the completion of the trial court, in this case also is very well known way of resolving the dispute resolution and of course family or deliberation is done outside the court. In everyday practice as the police investigator handling the case especially in traffic that cause others die can accept the settlement made out of court even though the case including the regular offense. Suggestion to write, so that the police be more assertive in dealing with cases like this.